Factors that influence artificial insemination with fresh semen in alpacas (Vicugna pacos) - Cardenas Suares, Nilton (2024)
The aim of the study was to evaluate factors that affect the fertility of artificial insemination (AI) with fresh diluted semen in alpacas. In Exp. 1, females with preovulatory follicles with diameters ≥7-≤ 9 or ≥10-≤12 mm were inseminated; in Exp. 2 the females were inseminated at 24, 26, 28 and 30 h after ovulation induction; In Exp. 3, alpacas were inseminated with semen at four concentrations: 15, 25, 35 and 45x106 sperm/ml; and in Exp. 4, using the best results from the previous experiments, 350 alpacas were inseminated in two peasant communities. Semen was collected by the post-copulatory method, using ejaculates with motility ≥60%, diluted in Tris-glucose-citric acid and egg yolk. Alpacas with preovulatory follicles ≥7 mm were selected for AI. Ovulation induction was done with a GnRH analogue and pregnancy diagnosis was made 30 days after service. Pregnancy rate was not affected by follicular size. AI 24 to 26 h after ovulation induction obtained a higher pregnancy rate (50 and 55%, respectively; p<0.05) compared to those inseminated at 28 and 30 h (35 and 30%). AI with 15x106 sperm/ml resulted in low pregnancy rates (30%) compared to 35 and 45x106 sperm/ml (50 and 55%, respectively). In the peasant communities, 55% pregnancy rate was obtained. The results suggest that the success of AI with fresh semen in alpacas is highly dependent on sperm dose and timing of insemination.